CGIAR Operations under the Plant Treaty Framework. Issue 3 (1st May 2019) - Noriega, Isabel López; Halewood, Michael; Abberton, Michael; Amri, Ahmed; Angarawai, Ijantiku Ignatius; Anglin, Noelle; Blümmel, Michael; Bouman, Bas; Campos, Hugo; Costich, Denise; Ellis, David; Gaur, Pooran M.; et al.
Abstract : The history of CGIAR and the development and implementation of the International Treaty on Plant Genetic Resources for Food and Agriculture ("Plant Treaty") are closely intertwined. In accordance with the agreements that 11 CGIAR centers signed with the Plant Treaty's Governing Body under Article 15 of the treaty, >730, 000 accessions of crop, tree, and forage germplasm conserved in CGIAR genebanks are made available under the terms and conditions of the multilateral system of access and benefit sharing, and the CGIAR centers have transferred almost 4 million samples of plant genetic resources under the system. Many activities of CGIAR centers and their genebanks (e.g., crop enhancement, improved agronomic methods, seed system strengthening, and capacity building) are influenced by, and promote, the Plant Treaty's objectives. The continued existence and optimal functioning of the Plant Treaty's multilateral system of access and benefit sharing is critically important to CGIAR in the pursuit of its mission. However, the multilateral system has encountered some challenges since the Plant Treaty came into force. The successful conclusion of the ongoing process for enhancing the functioning of the multilateral system could increase monetary benefit sharing and incentives for exchanging more germplasm. In the meantime, increased efforts are necessary to promote nonmonetary benefit sharing through partnerships, technology transfer, information exchange, and capacity building. These efforts should be integrated into countries' and organizations' work to implement the Plant Treaty's provisions on conservation and sustainable use of plant genetic resources, and farmers' rights.